THE NUMERAL ANALYTICAL METHOD WITH THE DISTRIBUTED CALCULATIONS FOR THE ANALYSIS OF THE TEMPERATURE FIELDS OF FLIP CHIP STRUCTURE - Levus, Yevheniya (International Journal of Computing, 2014)
The numeral analytical method of analysis of the temperature fields of Flip-chip structures is described in the article. The problem of time reduction of the temperature analysis procedure of microelectronic device is considered. A problem is of current importance, since a problem of providing necessary temperature condition of device functioning is solved through frequent implementation of the temperature fields analysis. One of the effective methods of solving this problem is the use of the distributed calculations. The calculable chart of the temperature analysis method is described with the use of mechanism of the distributed calculations. The presented results of calculations specify on efficiency of application of the distributed calculations with a coefficient equal to 1,5.